The Role of Strategic Partnerships in the Internationalisation of Small Born Global Firms - Paweł Capik; Andreas Brockerhoff (Entrepreneurial Business and Economics Review)
Objective: The article discusses motives driving the internationalisation of small born global firms and explores the role strategic partnerships play in the process. It argues that born globals are forced into international markets soon after their foundation due to limited domestic market capacity. Furthermore, they attempt to prevent competition on international markets and secure first mover advantages.